Analysing Security and Privacy Issues in Electronic Payment Transactions In E-Commerce Environment: A Qualitative Research on Saudis Consumers’ Behaviour In Saudi Arabia - Haya ALSHEHRI (Communications of International Proceedings, 2024)
Currently, e-commerce Business-to-Consumer (B2C) is vital for companies and is very popular in Saudi Arabia, although security and privacy concerns could pose several challenges to Saudis’ consumer behaviour. The current study goals to determine the actual interest of developing research investigates the impact of trust factors which are security and privacy on e-commerce payment transactions and the protection of customers’ privacy of personal information. The goal of this study is to examine how Saudi consumers have changed over the last eight years in relation to trust factors as security and privacy, the study adopts a qualitative approach via semi-structured interviews to enable in-depth information from 11 interviewers to facilitate a comparative analysis with the results obtained from outcomes eight years prior, this study will incorporate a newly developed model with updated outcomes. This enhancement aims to leverage the model's capabilities to advance B2C improvements within Saudi Arabia. The findings of this study indicate that most respondents expressed a high level of trust in well-established and large companies. While concerns regarding payment security persist, respondents demonstrated a willingness to make online payments through the available payment methods. The availability of alternative online payment options, beyond traditional credit cards, such as prepayment cards, Apple Pay, and third-party payment gateways like Sallah and Zid, is viewed positively. Most participants highlighted that their primary concern in marketing is ensuring the security and privacy of their payment information. Despite these apprehensions, they recognized a notable increase in trust over the past eight years, driven by advancements in technology. Consequently, all respondents observed an improvement in trust levels since these technological developments. Nonetheless, further research is advised to address additional trust-related concerns.
Keywords: E-Commerce; Business-to-Consumer (B2C); Saudi Arabia (SA); Trust; Security; Privacy.